2019
DOI: 10.1542/peds.2018-2418
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Mental Health Engagement From Primary Care: The Potential Role of Family Navigation

Abstract: Early engagement in mental health intervention is critical, yet the vast majority of children who are experiencing mental health concerns are not receiving needed services. Pediatric primary care clinics have been recognized as an ideal setting in which to identify and address mental health problems early, although engagement in mental health services within primary care and in community-based settings remains low. Navigators, or individuals with experience in navigating the mental health system, have been hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…Some of the strategies found to be helpful include the incorporation of motivational interviewing principles and attention to family stress, family coping, and broader family system issues. 46 Care navigators 47 and matching the race and ethnicity of clinical providers and families may also be helpful. 48 Finally, a recent review of 50 randomized controlled trials examining the effectiveness of treatment engagement interventions for child mental health services (conducted from 1974 to 2016) concluded that specific interventions can improve engagement and work across youths with varying racial and ethnic identifications, and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the strategies found to be helpful include the incorporation of motivational interviewing principles and attention to family stress, family coping, and broader family system issues. 46 Care navigators 47 and matching the race and ethnicity of clinical providers and families may also be helpful. 48 Finally, a recent review of 50 randomized controlled trials examining the effectiveness of treatment engagement interventions for child mental health services (conducted from 1974 to 2016) concluded that specific interventions can improve engagement and work across youths with varying racial and ethnic identifications, and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…In the same postal survey, (56) it was found that the perception of stigma associated with visiting a psychiatrist was one of the leading reasons that patients preferred seeing the GP for issues related to their mental illness. Other reports in the literature (69)(70)(71)(72)(73) have also cited stigma as a major factor preventing patients with mental illness from seeking help. Despite efforts to destigmatise mental illness, mental illness is still associated with significant stigma in Singapore.…”
Section: Less Stigmamentioning
confidence: 99%
“…Further investigation into barriers and facilitators of implementing widespread parent training in specific subpopulations of families is needed as well as the adaptation of existing parent training interventions to methods that may be more acceptable to families (e.g., web-based delivery, delivery over social media ;Baumann et al, 2015;Love et al, 2016). (Corrigan, Torres, Lara, Sheehan, & Larson, 2017;Godoy et al, 2019), including children (Lenaghan, O'Callaghan, Moss, Blackman, & Newcomb, 2018;Markoulakis et al, 2018). Family navigation interventions assist families in finding their way through the mental health care system by connecting families with the appropriate support and resources throughout their journey (Anderson & Larke, 2009).…”
Section: Implementing Parent Training May Promote Child Flourishmentmentioning
confidence: 99%
“…Family navigation interventions assist families in finding their way through the mental health care system by connecting families with the appropriate support and resources throughout their journey (Anderson & Larke, 2009). The family navigation model serves several needs, including collaboration amongst service providers and the family providing knowledge of services and evidencebased practices (Godoy et al, 2019). Furthermore, many family navigation models utilize peer mentors in which parents who have lived the experience of navigating the mental health system provide support and services to another parent (Godoy et al, 2019).…”
Section: Implementing Parent Training May Promote Child Flourishmentmentioning
confidence: 99%